2009
DOI: 10.1021/cg800802z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Calcium Oxalate Crystallization by Graft Copolymers

Abstract: Influence of graft copolymers with different architecture on spontaneous batch crystallization of calcium oxalate was investigated. The series of water-soluble polyethyleneglycol methacrylate-vinylsulfonic acid graft copolymers [(PEG-MA)-co-VS] and homopolymer of vinylsulfonic acid have been made, by radical polymerization, with defined molecular weight and structure. The presence of polymers inhibited the crystal growth of calcium oxalate possibly through adsorption onto the active growth sites for crystal gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 74 publications
2
14
0
Order By: Relevance
“…Furthermore, several new bands appeared at 24.4, 30.0, 35.6, and 38.2° between 5 and 40 days. According to the XRD standard comparison card, the bands belonged to the structure of calcium oxalate (CaC 2 O 4 ), which corresponded to the results in previous studies [51]. Additionally, the results from some researchers also showed that there was a close relationship between the fungi and calcium oxalates [52][53][54].…”
Section: Methods Of Compressive Strength Parallel To the Grainsupporting
confidence: 78%
“…Furthermore, several new bands appeared at 24.4, 30.0, 35.6, and 38.2° between 5 and 40 days. According to the XRD standard comparison card, the bands belonged to the structure of calcium oxalate (CaC 2 O 4 ), which corresponded to the results in previous studies [51]. Additionally, the results from some researchers also showed that there was a close relationship between the fungi and calcium oxalates [52][53][54].…”
Section: Methods Of Compressive Strength Parallel To the Grainsupporting
confidence: 78%
“…In Figure 6, it is possible to observe diffraction peaks that are attributable to both COD as COM crystals. However, more intense peaks, detected at 2θ, such as 15 • , 25 • , 30 • and 31 • , correspond to crystal planes {1 0 1}, {2 1 1}, {2 0 2} and {0 2 0} of COM crystals respectively, which confirm what is observed by the above analysis [43,[71][72][73][74]. In general, the use of this kind of functionalized DSPF film as a solid organic template could contribute to understanding the mechanisms underlying the formation of biologically important minerals, such as pathological urinary crystal forms, and it is kinetic on surface deposition.…”
Section: Resultssupporting
confidence: 84%
“…[11,38] There is a precipitation-dissolution equilibrium in water between the inorganic salts precipitation and the ions dissociated from precipitation. PASP/ASA holds a large number of À COOH, À SO 3 H and À CONHÀ , which can easily form a stable chelate [35] with cations in the water. Therefore, when PASP/ASA is added to a certain dosage in the solution, PASP/ASA can chelate with Ca 2 + to enhance the solubility of calcium scale in water and break the precipitation-dissolution equilibrium of calcium scale salts, effectively reducing the precipitation.…”
Section: Mechanism Of Scale Inhibitionmentioning
confidence: 99%